Interspecific Association between Iseilema anthephoroides and other Three Species in Grazing Grasslands of Ujjain - Dawar, K. M. Kiran; Singh, V. P. (Indian Forester, 1976)
The interspecific association between Iseilema anthephoroides and other 3 spp. of grasslands of Ujjain bave been determined by using Cochran's (1954) modification of Cole's(1949) formula. The degree of association was also determined by Cole's index. Positive association between Iseilema and Indigofera clearly indicates their same requirements and their interaction in such a way so as to favour mutual presence. Whereas negative association of Iseilema with Sporobolus and Paspalidium supports the idea of Anderson (1962) and Gause's (1932) i.e. presence of a number of microhabitats within a macrohabitat.